2004
DOI: 10.1111/j.1523-1755.2004.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of major involvement of human uroplakin genes in vesicoureteral reflux: Implications for disease heterogeneity

Abstract: Such a weak association and the lack of families with simple dominant Mendelian inheritance suggest that missense changes of uroplakin genes cannot play a dominant role in causing VUR in humans, although they may be weak risk factors contributing to a complex polygenic disease. The fact that no truncation or frame shift mutations have been found in any of the VUR patients, coupled with our recent finding that some breeding pairs of UP III knockout mice yield litters that show not only VUR, but also severe hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 44 publications
(30 reference statements)
3
42
0
Order By: Relevance
“…In particular, the exon 3 variant affecting a C/G conversion and a Pro154Ala change, reported to be associated with primary VUR (30), was found in a heterozygous state in five patients. This is equivalent to an allele frequency of 12.5%, which is slightly lower than the frequency previously reported in controls (16%) and individuals with primary VUR (25%) (30), although no statistical inference can be made from this small, ethnically diverse group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the exon 3 variant affecting a C/G conversion and a Pro154Ala change, reported to be associated with primary VUR (30), was found in a heterozygous state in five patients. This is equivalent to an allele frequency of 12.5%, which is slightly lower than the frequency previously reported in controls (16%) and individuals with primary VUR (25%) (30), although no statistical inference can be made from this small, ethnically diverse group.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the exon 3 variant affecting a C/G conversion and a Pro154Ala change, reported to be associated with primary VUR (30), was found in a heterozygous state in five patients. This is equivalent to an allele frequency of 12.5%, which is slightly lower than the frequency previously reported in controls (16%) and individuals with primary VUR (25%) (30), although no statistical inference can be made from this small, ethnically diverse group. The three previously reported UPIIIA mutations associated with severe bilateral renal adysplasia (20) were not observed in this cohort, and a PCR restriction fragment length polymorphism assay for the 818 C/T mutation showed that while the previously reported Patient 6 (this study) was a heterozygote, all other patients were homozygous for the wild-type allele.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The candidate gene approach had generally met with limited success in human VUR (e.g., screening of PAX2 or uroplakin genes) (32,33). Lu et al have, however, recently reported disruption of the ROBO2 gene in one patient with a balanced translocation and a phenotype that included VUR; in addition, mutational screening of patients with nonsyndromic VUR revealed two nonconservative amino acid substitutions (19).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in UPK3A have recently been found in some patients with renal aplasia, hypoplasia and dysplasia, including some who had vur. 121,122 By contrast, other investigators found no evidence for major involvement of UPK3A in vur, [123][124][125][126] but concede that their results do not rule out mutations in regulatory elements affecting gene expression or function. 123,126 The X chromosome some strong candidate genes on the X chromosome (KAL1 and AGT2R) as well as reports of X-linked transmission and evidence suggesting linkage of primary vur to the pseudoautosomal region 22 led Kelly et al 125 to investigate the possibility of linkage in these areas in a study in 2009.…”
Section: N a T U R E R E V I E W S U N C O R R E C T E D P R O O Fmentioning
confidence: 89%